Bimodal Probe for Magnetic Resonance Imaging and Photoacoustic Imaging Based on a PCTA‐Derived Gadolinium(III) Complex and ZW800–1. Issue 29 (10th July 2019) - Devreux, Marie; Henoumont, Céline; Dioury, Fabienne; Stanicki, Dimitri; Boutry, Sébastien; Larbanoix, Lionel; Ferroud, Clotilde; Muller, Robert N.; Laurent, Sophie
Abstract: Invited for the cover of this issue is the group of Sophie Laurent from the University of Mons, Belgium. The cover image shows a blood vessel containing the bimodal probe reported in this paper. Abstract : We synthesized a single probe molecule that is active in two imaging techniques, with very encouraging performance … Read more about the story behind the cover in the Cover Profile and about the research itself in the Full Paper by S. Laurent et al.